1996
DOI: 10.1071/mf9960685
|View full text |Cite
|
Sign up to set email alerts
|

Profile of a bloom of the cyanobacterium Cylindrospermopsis raciborskii (Woloszynska) Seenaya and Subba Raju in the Fitzroy River in tropical Central Queensland

Abstract: The physical, chemical and biotic conditions before and during a bloom of predominantly coiled heterocystous C. raciborskii are described. Initial increases in the population of this species were associated with windy days and the first downward movement of the thermocline into an anoxic hypolimnion after an extended period of stable stratification and no flow. Exponential growth and bloom formation coincided with the amval and retention of first wet-season inflows into the river impoundment. Cyanobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 24 publications
8
69
1
Order By: Relevance
“…This finding differs from other results, which reported a more narrow range of optimum light (75 to 125 μmol photons m -2 s -1 ) for strains isolated from a variety of sites (Dyble et al 2006;Bonilla et al 2012;Briand et al 2004). The ability of C. raciborskii to grow faster than other diazotrophic species under high light intensities is an important physiological feature (Fabbro & Duivenvoorden 1996;Briand et al 2004) that enhances their potential threat for water use, particularly in tropical regions.…”
Section: Growth Responsescontrasting
confidence: 56%
“…This finding differs from other results, which reported a more narrow range of optimum light (75 to 125 μmol photons m -2 s -1 ) for strains isolated from a variety of sites (Dyble et al 2006;Bonilla et al 2012;Briand et al 2004). The ability of C. raciborskii to grow faster than other diazotrophic species under high light intensities is an important physiological feature (Fabbro & Duivenvoorden 1996;Briand et al 2004) that enhances their potential threat for water use, particularly in tropical regions.…”
Section: Growth Responsescontrasting
confidence: 56%
“…The species can exploit high light conditions, as found in field (Fabbro and Duivenvoorden, 1996;Dokulil and Mayer, 1996) and experimental studies (Wu et al, 2009;Mehnert et al, 2010). Our analysis showed maximum C. raciborskii dominance of the phytoplankton in both low (z eu /z mix <0.2) and high (z eu /z mix >1) transparency conditions, reinforcing the species' capacity for success in different light environments due to its phenotypic plasticity (Piccini et al, 2011;Mehnert et al, 2012).…”
Section: Discussionmentioning
confidence: 62%
“…The specimens found for the most part had heterocyt so were fixing nitrogen. They were primarily the straight form (there is a high degree of morphological variability (FabbRo et al 1996, komáRek & komáRková 2003 and in the tropics akinetes or resting stages are rare but here immature akinetes were found so if they were successful in completing them it will enable them to over winter in our temperate climates. It has been reported that optimum temperatures for their akinete germination is 22-25°C (FabbRo & duivenvooden 1996) so given the adaptability of the organism it may or may not be able to germinate again in this river.…”
Section: Introductionmentioning
confidence: 99%